Clinical applicability and prognostic significance of molecular response assessed by fluorescent‐PCR of immunoglobulin genes in multiple myeloma. Results from a GEM/PETHEMA study. (3rd October 2013) - Martinez‐Lopez, Joaquin; Fernández‐Redondo, Elena; García‐Sánz, Ramón; Montalbán, María Angeles; Martínez‐Sánchez, Pilar; Pavia, Bruno; Mateos, María Victoria; Rosiñol, Laura; Martín, Marisa; Ayala, Rosa; Martínez, Rafael; Blanchard, María Jesus; et al.
Summary Minimal residual disease monitoring is becoming increasingly important in multiple myeloma (MM), but multiparameter flow cytometry (MFC) and allele‐specific oligonucleotide polymerase chain reaction (ASO‐PCR) techniques are not routinely available. This study investigated the prognostic influence of achieving molecular response assessed by fluorescent‐PCR (F‐PCR) in 130 newly diagnosed MM patients from Grupo Español Multidisciplinar de Melanoma (GEM)2000/GEM05 trials (NCT00560053, NCT00443235, NCT00464217) who achieved almost very good partial response after induction therapy. As a reference, we used the results observed with simultaneous MFC. F‐PCR at diagnosis was performed on DNA using three different multiplex PCRs: IGH D‐J, IGK V‐J and KDE rearrangements. The applicability of F‐PCR was 91·5%. After induction therapy, 64 patients achieved molecular response and 66 non‐molecular response; median progression‐free survival (PFS) was 61 versus 36 months, respectively (P = 0·001). Median overall survival (OS) was not reached (NR) in molecular response patients (5‐year survival: 75%) versus 66 months in the non‐molecular response group (P = 0·03). The corresponding PFS and OS values for patients with immunophenotypic versus non‐immunophenotypic response were 67 versus 42 months (P = 0·005) and NR (5‐year survival: 95%) versus 69 months (P = 0·004), respectively. F‐PCR analysis is a rapid, affordable, and easily performable technique that, in some circumstances, may be a valid approach for minimal residual disease investigations in MM.